Technology of biscuits, crackers, and cookies - Manley, D. J. R. (Duncan J. R.), 1938- (CRC Press ; Woodhead Pub., 2000)
Part 1 covers management issues such as quality management, process control and product development. Part 2 deals with the selection of raw materials and ingredients. The range of types of biscuit is covered in Part 3, while Part 4 covers the main production processes and equipment from bulk handling and metering of ingredients to packaging, storage, and waste management.